Parenting in the Digital Age: Implications to Physical, Social and Academic Life of Children in Various Age Groups - Paguirigan, Edmar Malsi; Paguirigan, Marjorie Janel Ramos (Jurnal Pendidikan Progresif, 2022)
Parenting in the Digital Age. Objectives: This study explores the parents' experiences in the digital age and determines the problems they encountered with children's use of digital technology, the different parenting styles they employed, and how they cope with the high-technology, fast-paced times that their children live in. Methods: It used a qualitative hermeneutical phenomenological approach. It strongly relies on the researcher's interpretations of their lived experience. Findings: The participants identified problems in discipline, academic, health, and social aspects of the child. Different parenting styles were employed by the participants but varied depending on the age of their children. Participants also highlighted their ways of managing children's misbehavior using digital technology. They set house rules like giving screen time, rewards and punishment, watching together, and open communication. Conclusion: Parents should find the right way to manage their children's misbehavior using digital technology and encourage their children to be with their friends and refrain from holding gadgets during playtime.  Keywords: Parenting styles, digital age, technology use.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202237